The calcium transporter ANNEXIN1 mediates cold‐induced calcium signaling and freezing tolerance in plants. (29th December 2020) - Liu, Qiangbo; Ding, Yanglin; Shi, Yiting; Ma, Liang; Wang, Yi; Song, Chunpeng; Wilkins, Katie A; Davies, Julia M; Knight, Heather; Knight, Marc R; Gong, Zhizhong; Guo, Yan; et al.
Abstract: The transient elevation of cytosolic free calcium concentration ([Ca 2+ ]cyt ) induced by cold stress is a well‐established phenomenon; however, the underlying mechanism remains elusive. Here, we report that the Ca 2+ ‐permeable transporter ANNEXIN1 (AtANN1) mediates cold‐triggered Ca 2+ influx and freezing tolerance in Arabidopsis thaliana . The loss of function of AtANN1 substantially impaired freezing tolerance, reducing the cold‐induced [Ca 2+ ]cyt increase and upregulation of the cold‐responsive CBF and COR genes. Further analysis showed that the OST1/SnRK2.6 kinase interacted with and phosphorylated AtANN1, which consequently enhanced its Ca 2+ transport activity, thereby potentiating Ca 2+ signaling. Consistent with these results and freezing sensitivity of ost1 mutants, the cold‐induced [Ca 2+ ]cyt elevation in the ost1‐3 mutant was reduced. Genetic analysis indicated that AtANN1 acts downstream of OST1 in responses to cold stress. Our data thus uncover a cascade linking OST1‐AtANN1 to cold‐induced Ca 2+ signal generation, which activates the cold response and consequently enhances freezing tolerance in Arabidopsis . Synopsis: How cold stress generates and controls transient elevation of calcium in the cytosol of plant cells is ill‐defined. Cold‐activated OST1 kinase promotes freezing tolerance in Arabidopsis by potentiating ANNEXIN1‐dependent calcium signaling. ANNEXIN1 (AtANN1) mediates the generation of cold‐triggered Ca 2+ signals. Cold‐activated OST1 kinase phosphorylates AtANN1 to enhance its Ca 2+ transport activity, thereby amplifying Ca 2+ signaling. OST1‐AtANN1 module regulates the expression of cold responsive CBF and COR genes and plant freezing tolerance. Abstract : Cold‐activated OST1 kinase phosphorylates ANNEXIN1 to boost calcium ion uptake and thus promotes expression of COR genes that enhance cold stress responses in Arabidopsis .